Commercial Gas Turbine Performance Analysis for Aviation Industries - Khairul Anuar, Muhammad Shahrir Arief; Abdul Ghafir, Mohammad Fahmi (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The existing turbofan seems to fit perfectly with the current airline’s demand, however, the performance of the engines can still be improved in a few aspects such as speed, fuel consumption, and component efficiency. Hence, the purpose of this study is to conduct performance analysis for available commercial gas turbine engines. The main objective of this study is to develop an engine model based on the available commercial gas turbines which then conduct a performance analysis on the engines. Another objective is to perform a comparison between the engine that had been analyzed. The study was simulated using GasTurb software. Two engines from commercial aircraft are determined first to ensure it is compatible to make a comparison for both engines. The engine is then analyzed using GasTurb and the result and data then exported into excel for further discussion. Both engine result from the performance analysis was then compared to determined which one is better. As a result, the highest thrust that GP7270 can produce is 372.157 kN while Trent 970-84 is 358.914 kN with the most altitude the thrust of Trent 970-84 is higher. The highest TSFC value for GP7270 13.044 g/(kN*s) while Trent 970-84 is 23.789 g/(kN*s). Fuel flow for both engines also significantly different with the highest fuel flow for GP7270 is 4.733 kg/s while Trent 970-84 is 8.538 kg/s. The propulsive efficiency also shows that Trent 970-84 have a higher value compare to GP7270 with a value of 0.771 and 0.578 respectively. Therefore, we could conclude that GP7270 is better compare to Trent 970-84 in terms of fuel efficiency even though Trent 970-84 could produce higher thrust and propulsive efficiency.